Demographics and Risk Factors for Non-Accidental Orthopedic Trauma. (June 2019) - Sivasundaram, Lakshmanan; Trivedi, Nikunj N.; Gatta, Julian; Ning, Anne Y.; Kim, Chang-Yeon; Mistovich, R. Justin
Childhood non-accidental trauma (NAT) is the second most common cause of death in children. Despite its prevalence, NAT is frequently unreported due to provider misdiagnosis or unawareness. The purpose of this study was to determine current risk factors and injury patterns associated with NAT. A retrospective review of the Kids' Inpatient Database was performed for the years 2009 and 2012. Univariate and multivariate analyses were used to determine the statistically significant risk factors for NAT. In 2009 and 2012, 174 442 children were hospitalized for fractures. Of these, 2.07% (3614) were due to NAT. Lower extremity (femur, tibia/fibula, foot), hand/carpus, clavicle, pelvis, and spine fractures were more likely to result from NAT; tibia/fibula fractures were most predictive of NAT. Children with anxiety, attention-deficit, conduct, developmental, and mood disorders were more likely to experience NAT. Those with cerebral palsy and autism were not at an increased risk for NAT.